Breaking the silence: Communication barriers in pentahelix collaboration for Borobudur’s tourism village - Lintang Muliawanti; Zulfikar Bagus Pambuko; Hikmawati Fajri Devi Safitri (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2025)
Community-based tourism development in Wanurejo Tourism Village demonstrates significant potential for enhancing well-being, preserving culture, and supporting local economic sustainability. This study aims to analyze communication barriers that cause disintegration in the Pentahelix collaboration for tourism development in Wanurejo Tourism Village, which serves as a buffer village for the Borobudur National Tourism Strategic Area (KSPN). The research employs a descriptive qualitative approach through Forum Group Discussions. The results indicate that despite the implementation of the Pentahelix model, optimal synergy and collaboration have not been achieved due to (1) a lack of communication accommodation, (2) overlapping roles and responsibilities among institutions, (3) unhealthy competition among tourism stakeholders, and (4) a lack of sustained involvement from the central and regional governments. This disintegrative communication negatively impacts the effectiveness of collaboration and community participation. This research suggests integration strategies that include enhancing inclusive communication, technology-based training, developing digital platforms, and policy reforms that support sustainable collaboration.